Experimental Method to Evaluate the Optical Properties of Aqueous Titanium Dioxide Suspensions - Satuf, María Lucila (2005)
The evaluation of the radiation field inside a slurry reactor constitutes a central step in the study of photocatalytic reactions. This task can be achieved by solving the radiative transfer equation (RTE) for the system under study. To solve the RTE, three optical properties of the catalyst suspensions are needed: the absorption coefficient, the scattering coefficient, and the phase function for scattering. In the present work, a novel experimental method to measure the optical properties of aqueous titanium dioxide (TiO2) suspensions is proposed. The method involved diffuse reflectance and transmittance spectrophotometric measurements of the catalyst suspensions, the evaluation of the radiation field in the sample cell, and the application of a non linear optimization program to adjust model predictions to experimental data. Three commercial brands of TiO2 were investigated: Aldrich, Degussa P25 and Hombikat UV 100.